Fabrication, microstructure, and properties of W–Cu graded composites - FENG Xiaowei; SI Anheng; FENG Bo; LI Daren (Fenmo yejin jishu)
The three-layer W–Cu graded composites were prepared by powders mixing and spark plasma sintering, using W and Cu powders in different proportions as the raw materials. The microstructure, interface characteristics, physical properties, mechanical properties, and thermal shock resistance of the W–Cu graded composites at different sintering temperatures were investigated. The results show that, the W–Cu graded composites sintered at 900 ℃ have the high relative density (95%) and retain the original design composition of single layer. The distribution of W and Cu in each graded layer is uniform, and the interface between W and Cu is well combined without diffusion. The mechanical properties of the W–Cu graded composites show the gradient distribution, and the microhardness of the W–40Cu layer is up to HV 136. The fracture is firstly present at the W–40Cu layer in the compression process, and the highest compressive yield strength is 378 MPa. The thermal conductivity of the W–Cu graded composite sintered at 900 ℃ is 202 W·m−1·K−1. After the thermal shock resistance test, the W–Cu gradient composites show the good thermal shock resistance performance without no crack at the interface.